Intervention of the Center for Child Studies and Protection Foundation in Preventing Child Violence Cases in Bale Village - Lisnawaty, Sri Dewi; Nurwahida Alimuddin; Dideng Kadir; Samintang; Ridwan (G-Couns: Jurnal Bimbingan dan Konseling, 2025)
This study analyzes the intervention of the PKPA Foundation in the prevention of child violence in Bale Village, Donggala Regency, using a descriptive qualitative method by collecting data through observation, interviews, and documentation. The informants involved include the Village Head, the Chairman of the Foundation, Foundation Staff, and the child's parents, who have an important role in the problem being investigated. The results of the study show that violence against children, whether physical, emotional, verbal, or neglect, has a significant impact on children's psychological development, such as anxiety, depression, and PTSD. This impact interferes with children's ability to manage emotions, form healthy interpersonal relationships, and increase the risk of social isolation. The PKPA Foundation implements prevention strategies that involve a community-based approach through education, community empowerment, and psychosocial support to victims. The Bale Village Government plays a role in strengthening local norms and building a community-based protection system. Based on these findings, it is suggested that further research measure the effectiveness of community-based approaches in preventing child violence in other areas with different social conditions. Researchers also need to explore the role and challenges of village governments in the implementation of child protection systems and analyze the long-term impact of violence on children, particularly in social and academic aspects after receiving interventions. Keywords: children, intervention, prevention, YPKPA, violence cases